1989
DOI: 10.1042/bj2620139
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and evaluation of non-steroidal mechanism-based inactivators of 3α-hydroxysteroid dehydrogenase

Abstract: Two non-steroidal mechanism-based inactivators for 3 alpha-hydroxysteroid dehydrogenase (3 alpha-HSD) of rat liver have been synthesized: 1-(4'-nitrophenyl)-2-propen-1-ol (I), and 1-(4'-nitrophenyl)-2-propyn-1-ol (II). Both of these compounds inactivate homogeneous 3 alpha-HSD in a time- and concentration-dependent manner only in the presence of NAD+. Analysis of the pseudo-first-order inactivation data gave a Kd of 1.2 mM for the allylic alcohol and a t1/2 (time required to promote a 50% loss of enzyme activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
13
0

Year Published

1990
1990
1999
1999

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…1 l(XIV)). This compound did not require oxidation to a ketone to cause enzyme inactivation, indicating that the powerful electron-withdrawing properties of the trifluoromethyl group were suffi¬ cient to activate the compound (Lawate & Covey 1990 (Ricigliano & Penning 1989 …”
Section: Introductionmentioning
confidence: 99%
“…1 l(XIV)). This compound did not require oxidation to a ketone to cause enzyme inactivation, indicating that the powerful electron-withdrawing properties of the trifluoromethyl group were suffi¬ cient to activate the compound (Lawate & Covey 1990 (Ricigliano & Penning 1989 …”
Section: Introductionmentioning
confidence: 99%
“…
The non-steroidal allylic and acetylenic alcohols 1-(4'-nitrophenyl)prop-2-en-l-ol (I) and l-(4'-nitrophenyl)prop-2-yn-lol (II) are oxidized by homogeneous 3a-hydroxysteroid dehydrogenase to the corresponding a/f-unsaturated ketones 1-(4'-nitrophenyl)prop-2-en-1-one (III) and 1-(4'-nitrophenyl)prop-2-yn-1-one (IV), which then inactivate the enzyme selectively with high affinity; low effective partition ratios are observed for the parent alcohols [Ricigliano & Penning (1989) Biochem. J.
…”
mentioning
confidence: 99%
“…It was found that in the absence of the lanthanide, the ethynylation reaction was a low yielding process. ethynyl magnesium bromide to nitroarylcarbonyls thereby improving the synthesis of tertiary α-acetylenecarbinols, which are useful substrates for biological studies [12]. The results of this investigation are here presented.…”
mentioning
confidence: 97%
“…The reaction proceeded smoothly at 0 °C to give the desired ethynyl carbinol 2a in nearly quantitative yield. Compound 2a had been previously prepared via p-nitrobenzaldehyde ethynylation with ethynyl lithium in 86% yield [12] and with ethynylmagnesium bromide (prepared from acetylene and methylmagnesium bromide.) in an unspecified yield [13].…”
mentioning
confidence: 99%
See 1 more Smart Citation